THE EFFECT OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE AERODYNAMICS, AEROELASTICS, AEROACOUSTICS LABORATORY (LA3-BRIN) IN THE SCIENCE AND TECHNOLOGY PARK BJ HABIBIE SETU, TANGERANG SELATAN - Rachmawan, Ade; Sunardi, Didi; Suherman , Asep (International Journal Multidisciplinary Science, 2025)
This study aims to analyze the influence of leadership style and work environment on employee performance at LA3-BRIN. The research employs a quantitative associative method with a saturated sampling technique, involving 80 employees as respondents. Data collection was conducted through questionnaires, and the analysis was carried out using multiple linear regression to examine both partial and simultaneous effects of the independent variables on employee performance. The findings reveal that leadership style does not significantly affect employee performance, while the work environment has a strong and positive influence. A well-structured and comfortable workplace, including air circulation, lighting, and noise control, enhances employee motivation and productivity. Although leadership style does not have a direct impact, it plays an indirect role in shaping organizational culture and engagement. The study concludes that improving the work environment and refining leadership approaches can enhance overall employee performance.